Genotyping of Cryptosporidium Parvum by PCR-Sequencing Analysis for The 70 Heat Shock Protein (HSP70) Gene and Dihydrofolate Reductase (DHFR) Gene - Sarmad Jassem Mohammed; Noora Amir Al-Watifi; Zahraa Isam Jameel; Amera Kamal Mohammed; Yusor Fadhil Alasadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cryptosporidium is an apicomplexan parasite that is increasingly recognized among immunocompetent hostsas a leading cause of childhood diarrhea in lower source settings and of waterborne diarrheal outbreaks inhigh income countries. C. parvum, which infects bovines, wild animals and humans, account for the majorityof human infections. Cryptosporidium oocysts are transmitted via the fecal oral route, including by person toperson spread, from contaminated food or water, or from contact with infected animals. 300 Stool sampleswere collected from patients in Hilla city from different hospitals. DNA extracted from stool samples, PCRamplification of DNA. Genotyping of HSP70 gene and DHFR Gene was performed using a polymerasechain reaction technique, followed by DNA sequencing. Accordingly, these DNA polymorphisms wereconfirmed using DNA sequencing. The sequencing results showed the presence of many SNPs determinedin the HSP70 gene and DHFR gene.